An Analysis of Product Quality, Variations, And Prices on Purchase Decisions Case Study of Suzuki Ertiga Car Dealer at PT. Trans Sumatera Agung, Medan City - Taufik Nopriansyah Pane; Daud Arifin; M.Husni Ritonga (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2022)
Car brand in the automotive market in Indonesia currently comes from Europe and Asia. Examples of these brands are Mitsubishi, KIA, Honda, Daihatsu, Suzuki, Ford, Proton, and Toyota. One of the most sold car variants in Indonesia is the MPV (Multi-Purpose Vehicle) types control nearly 60% of the national automotive market share. This is inseparable from the perception of the price of this type of family car which is relatively affordable for the middle class in Indonesia. (This study focuses on testing the consumer buying decision model for Multi-Purpose Vehicle (MPV) cars. The research model involves three independent variables, namely product quality, product variety and price, and the dependent variable of purchasing decisions. There are 90 respondents with criteria as car owners and visitors to PT. Trans Sumatra Agung (Suzuki Car Dealer Sisingamangaraja Hajosari II Medan Amplas) domiciled in Medan Indonesia. The data obtained were analyzed using the SPSS program. The results of the study found that three independent variables were proven to be able to positively and significantly influence consumer decisions in buying MPV cars. However, this study also found that, surprisingly, the product quality variable had a greater influence than the price and product quality variety variables. While the least influence on purchasing decisions is product variation. This study recommends the company management pay attention to the element of product quality, product variety, and price in preparing its promotional program to attract more consumers to buy Multi-Purpose Vehicle (MPV) cars.